2020
DOI: 10.1016/j.toxrep.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Placental microRNAs: Responders to environmental chemicals and mediators of pathophysiology of the human placenta

Abstract: Highlights miRNAs are important epigenetic regulators of placental gene and protein expression. miRNAs play a role in placenta developmental processes such as trophoblast invasion. Placental miRNAs are susceptible to exposure to environmental chemicals. miRNAs are involved in the pathogenesis of pregnancy-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 157 publications
0
20
0
Order By: Relevance
“…Over the past decade, considerable researches have been conducted on ncRNAs in pregnancy-related diseases, of which miRNAs play a central role. Dysregulation of miRNAs from the placenta was proved to influence placental progression and function and these miRNAs to export to the mother and fetus, thus directly affecting maternal and fetal physiology (77)(78)(79). Our data showed that many miRNAs (e.g., miR-191, miR-224, miR-374a, miR-193b, miR-365a, miR-4287, miR-590, miR-664b, miR-3622b, etc.)…”
Section: Discussionmentioning
confidence: 71%
“…Over the past decade, considerable researches have been conducted on ncRNAs in pregnancy-related diseases, of which miRNAs play a central role. Dysregulation of miRNAs from the placenta was proved to influence placental progression and function and these miRNAs to export to the mother and fetus, thus directly affecting maternal and fetal physiology (77)(78)(79). Our data showed that many miRNAs (e.g., miR-191, miR-224, miR-374a, miR-193b, miR-365a, miR-4287, miR-590, miR-664b, miR-3622b, etc.)…”
Section: Discussionmentioning
confidence: 71%
“…Several papers highlighted the relevant role of EVs released by decidual macrophages in the cross talk between fetal and maternal cells during pregnancy showing that the physiological balance between M1 and M2 phenotypes is essential during pregnancy (63). In this setting, miRNAs play a key role in human placental development at different levels during gestation, where dysregulation of miRNAs in both placenta and blood has been associated with maternal exposures to several toxicants (64).…”
Section: Discussionmentioning
confidence: 99%
“…When nicotine crosses through the placenta, binds to a-subunit of nAChRs, and activates them, then nAChRs increase intracellular calcium [Ca 2+ ] i that leads to intracellular signaling disconnection, apoptotic pathways activation, or organelle actions disruption which causes ROS production and then OS happens [ [44] , [45] , [46] ]. Also nicotine could change the expression of some placental microRNAs [ 47 ] which play several roles in many biological processes such as regulation of trophoblast differentiation, emigration, invasion, programmed cell death and angiogenesis [ 48 ]. Researches demonstrated that ethanol causes a decrease in the size of the zone and degenerative alterations in both labyrinthine and basal zones also interrupt blood flow [ 49 ].…”
Section: Discussionmentioning
confidence: 99%